1997
DOI: 10.1002/(sici)1097-0134(199703)27:3<459::aid-prot13>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Homology modeling of rabbit prolactin hormone complexed with its receptor

Abstract: The pituitary hormone prolactin (prl) is implicated in a number of biological functions, especially lactation, which is mediated through specific lactogenic receptors (PrlR). Human growth hormone (hGH) is also a pituitary hormone responsible for linear growth. While the growth hormone receptor (hGHR) binds only hGH, hPrlR can interact with both hGH and hPrl. Using structural information from the human growth hormone (hGH)/receptor (hGHR) complex, we modeled by homology a complex between rabbit prolactin hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…This ligand-independent homodimerization process has previously been reported for cytokine receptors [24]. Previous studies have shown that PRL stimulation induces a conformational change in the extracellular domain of the receptor that is necessary for optimum alignment and bonding of residues involved in dimerization [25,26]. This stabilizes the receptor dimer in a conformation that allows activation of cytoplasmic signaling cascades.…”
Section: Dimerization Of the Mutant Prl-r Is Required For Its Constitsupporting
confidence: 60%
“…This ligand-independent homodimerization process has previously been reported for cytokine receptors [24]. Previous studies have shown that PRL stimulation induces a conformational change in the extracellular domain of the receptor that is necessary for optimum alignment and bonding of residues involved in dimerization [25,26]. This stabilizes the receptor dimer in a conformation that allows activation of cytoplasmic signaling cascades.…”
Section: Dimerization Of the Mutant Prl-r Is Required For Its Constitsupporting
confidence: 60%